Cluster and Governance: Perception of Tourism Stakeholders in the City of Tangier - OUBAIH, Younes (International Journal of Scientific Research and Management (IJSRM), 2022)
This paper attempts to study the nature of the relationship between the cooperation of tourism actors in the form of a cluster and good territorial governance, through, first, the presentation of a literature review that deals with the different facets of this issue, and secondly, an exploratory qualitative study with tourism stakeholders in the city of Tangier, in order to assess the perception of stakeholders on the role that the tourism cluster could play as much as a territorial governance structure of the tourism sector of the city of Tangier.